Renewable energy powered rural community development centres in the developing countries - Islam, Mazharul; Amin, M. Ruhul; Islam, A.K.M. Sadrul (2006)
People in the developing countries who lack basic services and economic opportunities are primarily concerned with improving their living conditions. At present, unemployment problem in the rural areas of the developing countries are diversifying the moral values and social responsibilities of unemployed youth. To solve the problem, rural development centres (involving vocational training, IT services and other productive activities) can contribute significantly for the upliftment of these rural youths and can transform them into grass-root entrepreneurs. One critical factor hindering the establishment of such rural development centers is access to affordable and reliable energy services. Under this backdrop, environmentally benign renewable energy systems can contribute significantly in providing much needed energy in the unserved or underserved rural development centers in the developing countries to achieve both local and global environmental benefits. The paper demonstrates that energy deficient, economically backward communities in the off-grid areas of the developing countries, can be given an array of opportunities for income generation and social progress through rural development centers with the aid of renewable energy sources (such as wind, solar photovoltaics, solar thermal, biomass and micro-hydro), thereby improving their standard of living. Poverty alleviation in rural areas can be accomplished and the critical role of access to adequate level of energy services, Information Technology (IT) and modern communication facilities in it demonstrated. Furthermore, the production,implementation, operation and maintenance of renewable energy applications being labor-intensive, will also result in job growth in the village context, preventing migration of labor force, especially of young men, from rural areas to overcrowded industrial areas. An appropriately designed renewable energy systems can also have a significant role in reducing the impact of climate change through non production of green house gases.